One size fits all? A diversidade da gestão da diversidade - Crija, Débora Câmara (Universidade do Vale do Rio dos Sinos, 2022)
This dissertation proposes to understand how the diversity of form occurs in the dimensions of gender, race and functional diversity. To achieve this objective, we sought to map diversity management policies and practices of the dimensions covered in this study, analyze the attributes of the different dimensions of diversity and propose a framework with best practices for each dimension of diversity. For this, an descritive qualitative research was experimented with a single case study. The company Gama was selected because it is considered a reference in the management of diversity in the different dimensions. For data collection, in-depth interviews, document analysis and non-participant observation were carried out. From the study of diversity and the concepts of under different prisms, a framework and a toolkit were proposed for the intentional management of the diversity of the proposals in this study, reinforcing the importance of affirmative recruitment and intentional diversity management groups, where as minorities are protagonists.
Keywords: Diversidade; Gestão da diversidade; Programas de recrutamento afirmativos; Estrutura da diversidade; Gestão de pessoas; Diversity; Diversity management; Affirmative recruitment programs; Diversity framework; People management; ACCNPQ::Ciências Sociais Aplicadas::Administração